Varcarolis' manual of psychiatric nursing care planning : an interprofessional approach - Halter, Margaret J. (Margaret Jordan); Varcarolis, Elizabeth M. (St. Louis, Missouri : Elsevier, 2019)
This portable clinical companion provides you with the latest diagnostic information based on DSM-5 criteria. The "Manual" begins with an overview of psychiatric nursing care, continues with clinical chapters and associated with nursing care, and concludes with an overview of medical treatment approaches. This thoroughly updated, refreshed, and refined "Manual" provides essential information for clinical care. -- From publisher's description.
The nursing process -- Therapeutic relationships -- Therapeutic communication -- Neurodevelopmental disorders -- Schizophrenia spectrum disorders -- Bipolar disorders -- Depressive disorders -- Anxiety and obsessive-compulsive disorders -- Trauma-related disorders -- Eating disorders -- Sleep disorders -- Substance disorders -- Neurocognitive disorders -- Personality disorders -- Dying, death, and grief -- Suicide -- Crisis Intervention -- Anger, aggression, and violence -- Family violence -- Sexual violence -- Attention-deficit/hyperactivity medications -- Antipsychotics -- Mood-stabilizers -- Antidepressants -- Antianxiety medications -- Sleep promoting medications -- Substance use disorder medications -- Neurocognitive medications -- Psychotherapeutic models -- Brain stimulation therapies references -- Appendix A. Mental status assessment -- Appendix B. Assessment tools -- Appendix C. Development stages -- Appendix D. DSM-5 medical diagnoses.
Preceded by Manual of psychiatric nursing care planning / Elizabeth M. Varcarolis. Fifth edition. c2015.
Includes bibliographical references and index.
Keywords: Psychiatric nursing -- Handbooks, manuals, etc; Nursing care plans -- Handbooks, manuals, etc; Mental Disorders -- nursing; Nursing Assessment; Psychiatric Nursing -- methods; Plans de soins -- Guides, manuels, etc; Diagnostics infirmiers; Nursing care plans; Psychiatric nursing; Handbook; Handbooks and manuals; Handbooks and manuals; Guides et manuels